Holistic Approach for Cancer Patients: Integration of Therapeutic Gardens and Person Centered Care (Literature Review) - Ahyar Wahyudi; Listyo Yuwanto; Abdul Rofik (Formosa Journal of Science and Technology, 2023)
The concept of Person Centered Care (PCC) is a revolutionary approach in the world of health care that emerged from a strong argumentative foundation. PCC firmly recognizes that patients are not simply passive objects in the care process, but have the unique potential to be actively involved in managing their own health. This is based on deep psychological theories, one of which is the "self-efficacy" theory put forward by Albert Bandura. The Ecological Health Model is an approach that views a person's health from a more comprehensive and scientific perspective. This model explains that a person's health is not only influenced by physical factors, but also by a number of complex and interrelated social, psychological and environmental factors. In this understanding of health, socioeconomic conditions, social support, physical environment, and psychological factors all play an important role. A holistic approach to cancer patients that combines therapeutic gardens and person-centered care can provide substantial benefits. However, it requires active participation from patients, designers, healthcare professionals, and perhaps family members, to create a space that is truly healing and meets the unique needs of each individual on their healing journey.